LAW ON AGRICULTURAL COOPERATIVE COMPANIES IN ALBANIA; A REVIEW - Thomaj, Eneida (European Scientific Journal, ESJ, 2015)
This paper is oriented to thoroughly examine the provisions of the Law no. 38/2012, dated 05.04.2012 “On Agricultural Cooperative Companies”. In the first part of the paper it is analyzed how the cooperative company is established, the object of activity and quality of its members. Further, the paper deals with the organization structure of the agricultural cooperative companies by detailing its governing and managerial bodies, namely the general assembly and the administrator(s). In the second part of the paper it is conducted a brief comparison of the Albanian law on agricultural cooperative companies versus EU the like legislation having regard especially to the combination of financial and social aspects of various laws.